Rare Shewanella spp. associated with pulmonary and bloodstream infections of cancer patients, China: a case report - Zhang, Furong; Fang, Yujie; Pang, Feng; Liang, Shengnan; Lu, Xin; Kan, Biao; Xu, Jianguo; Zhao, Jinxing; Du, Yinju; Wang, Duochun (BMC infectious diseases, 2018)
Members of Shewanella species are opportunistic pathogens that are found in marine environments. Currently more than sixty species have been identified, whereas the most commonly clinical cases associated with Shewanella species have involved only two species, i.e., S. algae and S. putrefaciens. We present two cases of pulmonary and bloodstream infections caused by two rare Shewanella spp. strains from patients of gastrointestinal cancer. Two male patients with a history of gastrointestinal cancer presented to hospital with pulmonary and bloodstream infections, respectively. The infective pathogens of both cases were primarily isolated and identified as Shewanella algae (case I) and Shewanella putrefaciens (case II) by phenotypic features and VITEK 2 system, but they were further confirmed as Shewanella haliotis and Shewanella upenei by 16S rRNA gene sequence analysis. The major bacterial composition of the bronchoalveolar lavage in case I was also identified as Shewanella by 16S rRNA amplicon sequencing analysis. Antimicrobial susceptibility testing showed that the two strains had broad susceptibility, but S. haliotis in the case I was resistant to ciprofloxacin and levofloxacin and S. upenei in the case II was intermediate to imipenem, piperacillin/tazobactam and ciprofloxacin. To the best of our knowledge, this is the first cases of the pulmonary and bloodstream infections caused by Shewanella spp. from clinical patients in mainland China. Shewanella as a potential pathogen in China should not be ignored.